Cameroon Country Economic Memorandum : Markets, Public Administration, and Growth - World Bank (World Bank, Washington, DC, 2017)
To become an upper-middle income country by 2035, as targeted in its Vision 2035 document, Cameroon will have to increase productivity and unleash the potential of its private sector. Specifically, Cameroon’s real GDP must grow by around 8 percent and 5.7 percent in per capita terms over 2015–2035, which in turn will require the investment share of GDP to increase from around 20 percent of GDP in 2015 to 30 percent of GDP in 2035 and productivity growth to reach 2 percent over the same period, from its average rate of zero growth over the past decade. These are daunting yet doable challenges. To make it happen the public sector would need to reinvent itself and change its nature: reduce distortion, promote innovation and increase allocative efficiency; and more competitive markets would be needed to promote productivity gains. Based on the rigorous analysis of the Cameroonian economy using five main sources of data,1 the report will address the following topics: Chapter 1 analyzes constraints to growth, Chapter 2 explores constraints to enhance competitiveness, Chapter 3 examines the role played by the Cameroonian state on these constraints, and Chapter 4 derives from these analyses a set of actionable policy recommendations. The abstract contains the following structure: 1. Underpinnings of Cameroonian economy affecting growth potential 2. Recommendations on nine major areas of collaboration between the government and the private sector.